2005
DOI: 10.1080/00365520510011579
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of gastroesophageal reflux symptoms and esophagitis with or without symptoms in the general adult Swedish population: A Kalixanda study report

Abstract: GERS and EE (of which one-third is asymptomatic) are highly prevalent in the Swedish adult population. H. pylori infection seems to play a role in the manifestations of gastroesophageal reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
319
6
23

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 431 publications
(371 citation statements)
references
References 22 publications
23
319
6
23
Order By: Relevance
“…Diagnosing GERD as the cause of extraesophageal symptoms has proven to be very challenging. Upper endoscopy can document the presence of GERD when erosive esophagitis is present, but it is found in only one third of patients with GERD symptoms ( 126 ) and is even rarer aft er treatment with PPIs ( 59 ). Even when present, fi nding erosive esophagitis does not establish a diagnosis of GERD-related asthma, chronic cough, or laryngitis.…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…Diagnosing GERD as the cause of extraesophageal symptoms has proven to be very challenging. Upper endoscopy can document the presence of GERD when erosive esophagitis is present, but it is found in only one third of patients with GERD symptoms ( 126 ) and is even rarer aft er treatment with PPIs ( 59 ). Even when present, fi nding erosive esophagitis does not establish a diagnosis of GERD-related asthma, chronic cough, or laryngitis.…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…21 In contrast, NERD is more common in women. 2,7,15,16,34,39 A quantitative analysis of esophageal symptoms has showed that the symptom frequency and severity were significantly higher in women than in men. 8,36 On the other hand, the grade of esophagitis by esophagogastroduodenoscopy and the time period at pH below 4 during ambulatory 24-hour esophageal pH monitoring did not show any significant differences between men and women.…”
Section: Endoscopy-based Studymentioning
confidence: 99%
“…Gastroesophageal reflux symptoms (GERS) were defined as the presence of any troublesome heartburn and/or acid regurgitation over the past three months [14,17].…”
Section: Definitions Of Symptom Groupsmentioning
confidence: 99%